Differences in the Effectiveness of Watermelon Juice and Tomato Juice in Reducing High Blood Pressure in the Elderly Age 60-70 Years in the Work Area of the Cigeulis Health Center in 2022 - Mamah Muto’ah; Omega DR Tahun (Global Writing Academica Researching and Publishing, 2022)
Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest/calm. Increased blood pressure that lasts for a long time (persistent) can cause damage to the kidneys (kidney failure), heart (coronary heart disease) and brain (cause stroke) if not detected early and receive adequate treatment. To find out the difference in the effectiveness of watermelon juice and tomato juice in reducing high blood pressure in the elderly aged 60-70 years in the working area of ​​the Cigeulis Health Center in 2022. Analytical with cross sectional approach. The sample in this study were 30 elderly people at the Cigeulis Health Center in November 2022 (total sampling). There is an effect of Tomato Juice which is proven to be effective in reducing blood pressure (p value 0.000<0.05), there is an effect of Watermelon Juice which is proven to be effective in reducing blood pressure (p value 0.000<0.05). From the results of the study it turned out that these two variables were equally effective in reducing blood pressure because the p value was 0.000 <0.05. It is expected that the puskesmas will provide education on the prevention and management of hypertension. To prevent hypertension and reduce blood pressure red watermelon and tomatoes.